Professional development model for language teachers in junior high schools in Anhui province, China - Ding, Jie; Boonphadung, Suttipong (Edelweiss Applied Science and Technology, 2025)
Junior high school language education is undergoing a reform that prioritizes the development of students’ language literacy, extending traditional language and literature instruction. Teacher professional development (PD) is crucial for ensuring the effective implementation of this approach. However, in the context of junior high school language education reform, studies regarding how language instruction promotes students' moral development, addresses the unequal distribution of educational resources between urban and rural areas, and enhances teacher quality are limited. Against this backdrop, the purpose of the present study is to investigate the administrative context, PD level, and influencing factors of PD among junior high school language teachers in Anhui Province, and propose a PD model for language teachers. Based on data from 598 respondents, this study employs a mixed-methods approach, integrating qualitative interviews, quantitative surveys analyzed with AMOS, and focus group discussions. The findings indicate that individual teacher factors (ITF) and educational authority factors (EAF) have significant positive direct effects on teacher’s PD guide (TPGD). Furthermore, school management factors (SMF) also have a significant positive direct effect on TPGD. Additionally, SMF was found to mediate the relationships between ITF and TPGD, as well as between EAF and TPGD, indicating significant indirect effects of ITF and EAF on TPGD through SMF. This study highlights the need for greater support and opportunities to address challenges such as limited professional pursuit, ensuring quality language education. The proposed PD model offers valuable insights into effectively supporting language teachers' PD, with implications for policy and practice.